If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4x(x + -2) = 4x + -5 Reorder the terms: 3x + 4x(-2 + x) = 4x + -5 3x + (-2 * 4x + x * 4x) = 4x + -5 3x + (-8x + 4x2) = 4x + -5 Combine like terms: 3x + -8x = -5x -5x + 4x2 = 4x + -5 Reorder the terms: -5x + 4x2 = -5 + 4x Solving -5x + 4x2 = -5 + 4x Solving for variable 'x'. Reorder the terms: 5 + -5x + -4x + 4x2 = -5 + 4x + 5 + -4x Combine like terms: -5x + -4x = -9x 5 + -9x + 4x2 = -5 + 4x + 5 + -4x Reorder the terms: 5 + -9x + 4x2 = -5 + 5 + 4x + -4x Combine like terms: -5 + 5 = 0 5 + -9x + 4x2 = 0 + 4x + -4x 5 + -9x + 4x2 = 4x + -4x Combine like terms: 4x + -4x = 0 5 + -9x + 4x2 = 0 Factor a trinomial. (1 + -1x)(5 + -4x) = 0Subproblem 1
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Subproblem 2
Set the factor '(5 + -4x)' equal to zero and attempt to solve: Simplifying 5 + -4x = 0 Solving 5 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -4x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 0 + -5 -4x = 0 + -5 Combine like terms: 0 + -5 = -5 -4x = -5 Divide each side by '-4'. x = 1.25 Simplifying x = 1.25Solution
x = {1, 1.25}
| 8t-10-3t=20 | | H=9piem | | 1+1+X=69 | | 242/b=44 | | 3n-2÷5=7/10= | | (-3)+(-15)= | | 15x+5+(22x+4)=120 | | 3(3)+2y=9 | | 13=x^2-0.20x | | 9x^2+18x+45=0 | | 2(2x+5)-5x=12 | | 2.9=-2b+0.5 | | 13x+4y=39 | | 6-3x=5x+94 | | 3y+-1=17 | | 3h^2-39h=-126 | | 9x+2=101 | | 0.6p+4=0.3(p+5)+0.3(p+1) | | 12x+1=111 | | 3x^2-6x=-25 | | 2n+8=136+4n | | 5x+4-6=72 | | 6x+9=5x+2 | | -7x-9+y=3 | | 6x-12x=-6 | | 0.35x+0.30(240-x)=76.25 | | 2.40x=30 | | 5x+4-6= | | 0+3z= | | f(x+9)=x^2+8x-8 | | 52=7x+7x+10 | | 6m+4s=32 |